International Electron Devices Meeting 1998. Technical Digest (Cat. No.98CH36217)
DOI: 10.1109/iedm.1998.746312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1 nm-thick structural "strained-layer" near SiO/sub 2//Si interface on sub-4 nm-thick gate oxide reliability

Abstract: The relationship between the structural property and the electrical characteristics of thin Si02 below 4nm is investigated. The structural "strained-layer" near SiOz/Si interface is confirmed to affect strongly the TDDB (Time Dependent Dielectric Breakdown) lifetime of the thin gate oxides. The increase of the built-in comprcssive strain analyzed by the XPS (X-ray Photoelectron Spectroscopy)-based technique is experimentally found to decrease the TDDB lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…The CVD-Si3N4 stack gate dielectric with SiON as a base layer has attracted much attention recently in the direct tunneling regime(2)(3). It is also well known that the strained layer within lnm thick at Si02/Si interface strongly affects the gate oxide reliability (4). One can expect that this strained layer will limit the scaling of future stack gate dielectrics, since the thickness of base layer for stack dielectric reported so far is around lnm.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The CVD-Si3N4 stack gate dielectric with SiON as a base layer has attracted much attention recently in the direct tunneling regime(2)(3). It is also well known that the strained layer within lnm thick at Si02/Si interface strongly affects the gate oxide reliability (4). One can expect that this strained layer will limit the scaling of future stack gate dielectrics, since the thickness of base layer for stack dielectric reported so far is around lnm.…”
Section: Introductionmentioning
confidence: 98%
“…The physical analysis of the dielectrics is mainly performed by the angle-resolved X-ray photoelectron spectroscopy (XPS) (4). The N profile in SiON base layer is determined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In the STL, the existence of suboxides (Si 2 O, SiO, and Si 2 O 3 ) has been previously identified to exist by x-ray photoelectron spectra. 10,11 The built-in compressive strain in the Si-O bonds causes the reduction of the Si-O-Si average bond angle or the Si-Si second neighbor distance. 10,12 In addition, the Si-H bond which results mainly from post-metal anneal in forming gas ambient and the stretched Si-O bond in the STL are proposed to be the precursor of oxide breakdown 13 and is believed to be responsible for the temperature dependence of oxide breakdown.…”
mentioning
confidence: 99%
“…10,11 The built-in compressive strain in the Si-O bonds causes the reduction of the Si-O-Si average bond angle or the Si-Si second neighbor distance. 10,12 In addition, the Si-H bond which results mainly from post-metal anneal in forming gas ambient and the stretched Si-O bond in the STL are proposed to be the precursor of oxide breakdown 13 and is believed to be responsible for the temperature dependence of oxide breakdown. 3,14 It has been reported that the temperature dependence of oxide breakdown can be ascribed to both atomic and molecular hydrogen diffusion released from Si-H bond breaking caused by the anode hole injection 3,15 and that the presence of the compressive strain will lower the diffusion barrier of those hydrogen-related species.…”
mentioning
confidence: 99%
See 1 more Smart Citation